THE TEACHING OF TOEFL TEST PREPARATION ATRAM ENGLISH COURSE - NIDLAM HABIBY, AHMAD (RETAIN : Journal of Research in English Language Teaching, 2015)
Abstrak TOEFL adalahujian yang dikelolaolehEducational Testing Sevice (ETS - www.ets.org), sebuahperusahaanswasta yang terletak di Princeton, New Jersey, yang mendirikan TOEFL, dandigunakanuntukmengevaluasikemampuanaslibahasaInggrispembicara non natifbahasaInggris (Gear, Jolene: 2009). KemahiranpembicarabahasaInggrisyang bukannatifdinyatakandalambentukangka (skor). Skortersebutditerimadenganmengambiltes TOEFL. Tesitusendiri, termasuksemuakegiatan yang berkaitandengantes TOEFL, ditanganioleh ETS, dan / ataulembagaapa pun yang telahditunjukoleh ETS. Namun, ETS tidakmenetapkannilai yang diperlukanuntukmasukkeuniversitastertentu, perguruantinggi, sekolah, ataudepartemen. Keputusan yang dibuatolehlembaga-lembagapendidikanindividu (Hinkel, Eli: 2004). TOEFL Paper-Based (PBT) adalahtespensildankertas (J. Sharpe, Pamela: 2008). Inimenuntutkertassebagai media danpensilsepertimenulisalat. Kertas-kertastersebutadalahlembarpertanyaandanjawabansementarapensil yang digunakanuntukmenjawabpertanyaan-pertanyaandenganmenyilangkandan / ataumengarsirpilihanjawaban di lembarjawaban. Hal inisepertitestertulisbiasa yang sangatumum di sekolah-sekolah, khususnya di Indonesia. Irham Ali Saifuddin (2007) mengatakanbahwa PBT adalahtes TOEFL yang paling umumdandigunakan di negaraini. Kota tempatpenelitiandilakukan, Gresik, menggunakan PBT. SehinggapenelitianiniadalahtentangpengajaranTOEFL PBT. PenelitianinimerupakanpenelitiandeskriptifkualitatifdanbertujuanuntukmendeskripsikanInstruktur TOEFL RAM English Course dalammengajarkanpersiapan TOEFL. Penelitimenggunakan Survey, Kuesioner, danWawancarasebagaiinstrumenpenelitianini. Hasilpenelitianmenunjukkanbahwainstruktur TOEFL RAM English Course memilikimetodesendiridalammengajarpersiapan TOEFL. Responsiswajugapositif. Merekamendapatpeningkatannilai di pos-testerakhirtentusajadibandingkandenganpra-tesmereka. Kata Kunci: Pengajaran, TOEFL, persiapan, PBT, RAM English Course. Abstract TEOFL is an examination that is administered by the Educational Testing Service (ETS – www.ets.org), a private company that is located on Princeton, New Jersey, that found TOEFL, and is used to evaluate a nonnative English speaker’s proficiency in the English language (Gear, Jolene: 2009). The proficiency of the nonnative English speakers is expressed in the form of number (score). The score is received by taking the TOEFL test. The test itself, including the all activities related to the TOEFL test, is handled by ETS, and/or any institutions that has been designated by ETS. However, the ETS does not establish the scores necessary for admission to particular universities, colleges, schools, or departments. The decisions are made by the individual education institutions (Hinkel, Eli: 2004). The Paper-Based TOEFL (PBT) is a pencil-and-paper test (J. Sharpe, Pamela: 2008). It demands papers as the media and pencils as writing tool. The papers would be the question and answer sheets while pencils are used to answer the questions by crossing and/or shading the multiple choice answer in the answer sheet. It is like the ordinary written tests that are very common in schools, especially in Indonesia. Irham Ali Saifuddin (2007) said that PBT is the most prevalent and used TOEFL test in this country. The city where the research was conducted, Gresik, uses PBT. So that the research was about TOEFL PBT Teaching. This is a descriptive qualitative research and this research aimed to describe the TOEFL Instructor of RAM English Course teach the TOEFL preparation. The researcher used Survey, Questionnaire, and Interview as the instrument of this research. The results of the study showed that the TOEFL instructor of RAM English Course has his own method in teaching TOEFL preparation. The students’ response is also positive. They got increased score in the last post-test of the course compared with their pre-test Keywords: Teaching, TOEFL, preparation, PBT, RAMEnglish Course